Augmentation of Apoptosis and Tumor Regression by Flavopiridol in the Presence of CPT-11 in Hct116 Colon Cancer Monolayers and Xenografts - MOTWANI, Monica; JUNG, Christoph; SIROTNAK, Francis M; YUHONG SHE; SHAH, Manish A; GONEN, Mithat; SCHWARTZ, Gary K (Clinical cancer research, 2001)
CPT-11, a DNA topoisomerase I inhibitor, has demonstrated clinical activity in colorectal cancer. Flavopiridol, a cyclin-dependent kinase inhibitor, is rapidly emerging as a chemotherapy modulator. To enhance the therapeutic index of CPT-11 in colon cancer, we studied the combination of these two drugs in relatively resistant human colon cancer cells, Hct116. Exposure of parental Hct116 cells to clinically achievable concentrations of SN-38 (the active metabolite of CPT-11) induces p21 and a G 2 arrest. However, these conditions fail to induce apoptosis. In contrast, Hct116 cells that are p21 deficient (p21−/− Hct116) readily undergo apoptosis after treatment with SN-38. In this study we show that the parental Hct116 cells can be sensitized to undergo apoptosis by the addition of flavopiridol after SN-38 treatment. The induction of apoptosis was greatest with sequential therapy consisting of SN-38 followed by flavopiridol. Clonogenic assays also showed greatest inhibition with this sequence. Sequential treatment with SN-38 followed by flavopiridol was associated with higher activation of caspase-3 and greater cleavage of both p21 and XIAP, an inhibitor of apoptosis, compared with other treatment schedules. CPT-11 induced some tumor regressions but no complete responses in the p21-intact Hct116 xenografts. CPT-11 with flavopiridol more than doubled tumor regression, compared with CPT-11 alone, and produced a 30% complete response rate. Our studies indicate that CPT-11 induces cell cycle arrest rather than cell death and that flavopiridol, by activating the caspase cascade, cleaves the inhibitors of apoptosis and sensitizes the cells to undergo cell death. Thus, flavopiridol combined with CPT-11 may provide a completely new therapeutic approach in the treatment of colon cancer.